TELAAH ALTERNATIF MODEL MOTIVASI UNTUK MENINGKATKAN KINERJA PERUSAHAAN - Meirezaldi, Onni (Profit: Jurnal Adminsitrasi Bisnis, 2007)
In order to developing human resource to improve of company performance, expanding some motivation model based on by former motivation theories. There are two big groups of motivation theory, which is content theory assuming that internal factor of individual will give energy to sustain process theory and behavior assuming that behavior represents result of individual decision- making processes. Reaching company performance which is maximal to be needed the understanding of the motivation models so that can be made by direction to motivate employees.Keywords: Motivation, Performance, QWL